Perancangan Mesin Vibration Deburring Untuk Penghalusan Sudut Tajam Pada Benda Kerja Logam Di PT.XYZ - Yuhana Dwi Prasetya; Amirul Siddiq Mirza; Luqman Nur Hakim (CV. Multi Kreasi Media, 2025)
Machining processes such as cutting, drilling, and grinding often leave burrs on workpiece edges that can reduce surface quality, disrupt assembly, and pose safety risks. Therefore, an effective and efficient finishing method is required to remove these burrs. This study aims to design a vibration deburring machine capable of removing burrs while improving the surface quality of machined workpieces. The design method includes a literature review and analysis of existing products as design references, identification of functional requirements and technical specifications, calculation of main components, and mechanical and frame structure design. The proposed vibration deburring machine is driven by a three-phase electric motor with a rotational speed of 3000 RPM and a power of approximately 1 kW. The deburring tank is designed with dimensions of 700 × 440 × 400 mm, enabling the processing of ten or more workpieces in a single cycle. The machine frame is constructed from ASTM A36 steel with a yield strength of 250 MPa. Structural analysis shows that under a maximum load of 300 kg, the highest stress in the lower frame reaches 69.5 MPa, which is well below the material’s yield limit. Based on these results, the designed vibration deburring machine meets operational and structural strength requirements. This design is expected to serve as an alternative solution and reference for vibration-based finishing machines in industrial manufacturing applications. The machine is suitable for small-scale manufacturing.